(untitled) (International Journal of Social Sciences and Humanity Development, 2025)
Background: Since 2016, Uzbekistan has initiated a fundamental shift in its foreign policy under the leadership of President Shavkat Mirziyoyev, moving away from a protracted period of isolationism toward a strategy of proactive regional engagement. A central pillar of this new doctrine is the use of economic diplomacy to resolve disputes, foster goodwill, and enhance its influence within Central Asia, a region historically characterized by complex geopolitical dynamics and fragmented cooperation. Objective: This article analyzes the mechanisms and outcomes of Uzbekistan's economic diplomacy. It seeks to demonstrate how targeted policies in trade, infrastructure, and energy are associated with the nation's elevated status as a pivotal regional actor. The study investigates the hypothesis that this strategic deployment of economic statecraft is the primary factor linked to its growing influence. Methods: The study employs a qualitative, descriptive research design, conducting a systematic analysis of policy documents and official reports. Sources are drawn from the Government of Uzbekistan [7], alongside major international institutions including the World Bank [10], IMF [3], Asian Development Bank [1], and various United Nations agencies [8, 9]. Thematic analysis was used to identify key strategies and their corresponding results, while a comparative approach contextualizes Uzbekistan's efforts within the broader regional framework, particularly in relation to Kazakhstan [4, 6]. Results: The findings indicate that Uzbekistan's diplomatic efforts are correlated with significant positive outcomes. These include a marked increase in intra-regional trade, the successful launch of critical cross-border infrastructure projects that enhance connectivity, and strengthened cooperation in the crucial sector of energy security. However, the analysis also identifies significant internal challenges, such as persistent bureaucratic inefficiencies [2], that could impede the long-term sustainability of these achievements. Conclusion: Uzbekistan's strategic deployment of economic statecraft is strongly associated with its effective repositioning as an influential leader in Central Asia. By prioritizing economic cooperation, Tashkent has successfully built political capital and fostered a more stable and integrated regional environment. Sustaining this momentum appears to be contingent on a concerted focus on deepening domestic institutional reforms.